Adolescent criminality: multiple adverse health outcomes and mortality pattern in Swedish men - Marlene Stenbacka; Tomas Moberg; Jussi Jokinen (BMC, 2019)
Abstract Background To investigate the impact of adolescent violent and non-violent criminality and subsequent risk of morbidity and mortality in adulthood in a large Swedish cohort of young men conscripted for military service in 1969/70. Methods The cohort consisted of 49,398 18-year-old Swedish conscripts followed up for morbidity and mortality up to the age of 55 years in Swedish national registers. Information about convictions for crime before conscription was obtained from national crime registers. Data from a survey at conscription were scrutinized to get information on potential confounders. Results Hospitalization due to alcohol and drug related diagnoses and attempted suicide were significantly more evident in the violent group compared to non-violent criminals and non-criminals. More than one fifth (21.13%) of the young violent offenders, 12.90% of the non-violent offenders and 4.96% of the non-criminals had died during the follow-up period. In Cox proportional multivariate analyses, young violent offenders had twice the hazard (HR = 4.29) of all-cause mortality than the non-violent offenders (HR = 2.16) during the follow-up period. Alcohol and drug related mortality, suicide and fatal accidents were most evident in both violent and non-violent offenders. Conclusions Men with adolescent criminality received more inpatient care due to alcohol and drug related diagnoses and attempted suicide as adults. Mortality due to unnatural causes, alcohol, and drug related diagnoses, suicide and accidents was most evident in violent offenders, while these causes of death were much lower in non-criminals. Men with adolescent criminality are a high-risk group for multiple adverse health outcomes and for early death. Efforts for detection of substance use and psychiatric disorders in this group is important for the prevention work in both local- and community levels as well as national prevention programs.